2013
DOI: 10.1016/j.bbamcr.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

N-terminally truncated forms of human cathepsin F accumulate in aggresome-like inclusions

Abstract: The contribution of individual cysteine cathepsins as positive mediators of programmed cell death is dependent on several factors, such as the type of stimuli, intensity and duration of the stimulus, and cell type involved. Of the eleven human cysteine cathepsins, cathepsin F is the only cathepsin that exhibits an extended N-terminal proregion, which contains a cystatin-like domain. We predicted that the wild-type human cathepsin F contains three natively disordered regions within the enzyme's propeptide and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…To date, nine mutations with recessive inheritance are known to cause CLN13: six missense mutations (p.Gln321Arg, p.Gly458Ala, p.Ser480Leu, p.Tyr231Cys, p.Ile404Thr, and p.Cys326Phe), a nonsense mutation c.416C > A (p.S139*), a frameshift mutation (p.Ser319Leufs*27), and a mutation preventing the correct splicing of CTSF mRNA (c.213 + 1G>C) [134][135][136][137]. It has been shown that disease-causing CTSF mutants fail to cleave the lysosomal integral membrane protein type-2 (LIMP-2/SCARB2) required for normal biogenesis and maintenance of lysosomes and endosomes [138,139]; however, the exact mechanism by which CTSF deficiency translates in the clinical onset of CLN13 remains elusive. The biochemical and molecular mechanisms underlying NCLs have not been addressed yet.…”
Section: Gene Deficiency Biological Effect Referencesmentioning
confidence: 99%
“…To date, nine mutations with recessive inheritance are known to cause CLN13: six missense mutations (p.Gln321Arg, p.Gly458Ala, p.Ser480Leu, p.Tyr231Cys, p.Ile404Thr, and p.Cys326Phe), a nonsense mutation c.416C > A (p.S139*), a frameshift mutation (p.Ser319Leufs*27), and a mutation preventing the correct splicing of CTSF mRNA (c.213 + 1G>C) [134][135][136][137]. It has been shown that disease-causing CTSF mutants fail to cleave the lysosomal integral membrane protein type-2 (LIMP-2/SCARB2) required for normal biogenesis and maintenance of lysosomes and endosomes [138,139]; however, the exact mechanism by which CTSF deficiency translates in the clinical onset of CLN13 remains elusive. The biochemical and molecular mechanisms underlying NCLs have not been addressed yet.…”
Section: Gene Deficiency Biological Effect Referencesmentioning
confidence: 99%
“…In contrast to type 10 CLN, the stored protein is unknown . The mechanism by which mutations in this lysosomal cysteine protease (MEROPS ID: C01.018) gene, which is mainly associated with lysosomal degradation and autophagy , cause this adult‐onset CLN is completely obscure. In any case, the slow progression of the disease argues for a mild effect on CTSF function or for a partial compensation of its loss‐of‐function.…”
Section: Cathepsins D and F Deficiencies Are Associated With Two Distmentioning
confidence: 99%
“…Human CTSF propeptide consists of a signal peptide, a cystatin-like domain, an I29 inhibitor domain, and a mature form of cathepsin F (Jeric et al, 2013). Previous studies have revealed the cysteine-cathepsin-related activation of programmed cell death (apoptosis) (Guicciardi et al, 2004; Repnik et al, 2012), but the physiological functions of CTSF have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the human genome, 11 different cysteine cathepsins have been characterized (cathepsins B, C, F, H, K, L, O, S, V, X, and W) via bioinformatics analysis (Rossi et al, 2004). Among them, CTSF has an extended N-terminal proregion, which contains a cystatin-like domain (Ahn et al, 2009; Jeric et al, 2013). Similar to cathepsins B, C, H, L, O, and Z, CTSF is ubiquitously expressed in widespread tissues, whereas cathepsins J, K, S, and W are expressed in restricted tissues or cell types (Tang et al, 2006; Turk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%